1990
DOI: 10.1093/ptj/70.3.150
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Derived Measurements of Leg-Length Differences Obtained by Use of a Tape Measure

Abstract: Determining the difference in the length of an individual's legs is often an important component of a musculoskeletal examination. Although measurements are easily obtained with a tape measure, the validity of these measurements is not known. The purpose of this study was to examine the validity of determinations of leg-length differences (LLDs) obtained by use of a specified tape measure method (TMM). Leg-length differences using the TMM and a radiographic technique were determined for 10 subjects who were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
1
18

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 9 publications
3
101
1
18
Order By: Relevance
“…While using a tape measure is an easy, safe, and noninvasive means of assessing LLD, it is less reliable when compared to radiographic techniques such as a scanogram [7,8,10,43]. The average of two tape measurements of the distance between the ASIS and medial malleolus appears to have acceptable validity and reliability when used as a screening tool for assessing LLD [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While using a tape measure is an easy, safe, and noninvasive means of assessing LLD, it is less reliable when compared to radiographic techniques such as a scanogram [7,8,10,43]. The average of two tape measurements of the distance between the ASIS and medial malleolus appears to have acceptable validity and reliability when used as a screening tool for assessing LLD [14].…”
Section: Discussionmentioning
confidence: 99%
“…Despite high interobserver reliability of the true (ICC, 0.99) and apparent (ICC, 0.88) methods of clinically assessing LLD, the concordance between the true measurement and radiographic assessment (ICC, 0.80) and apparent method and radiographic assessment (ICC, 0.75) was lower. In a prospective study of 10 adults with LLD and nine asymptomatic volunteers, Beattie et al [7] compared the variability of measurements using tape measure with a scanogram. A single examiner examined the LLD of all 19 subjects using a tape measure from the ASIS to medial malleolus on two separate occasions and compared the clinical results with those obtained using a scanogram.…”
Section: Clinical Techniquesmentioning
confidence: 99%
“…Tape measures have routinely been used to assess LLD in clinical practice (44 -47). Contrary to the findings of this review, the validity of this technique has been demonstrated in other populations, including in people with lower back pain and in healthy people (48,49). It is possible that the use of a single tape measurement of LLD in the study included in this review may have influenced the validity of this test, since it previously has been recommended that a mean score from 2 trials be used for measuring LLD (48).…”
Section: Dobson Et Almentioning
confidence: 56%
“…Subjects included in this study did not have a history of low back pain, with no reports of osseous or joint injuries in the lower limbs (LL) in the six months that preceded the evaluation. Moreover, the subjects were excluded from this study when they had a real leg length discrepancy, as clinically measured 21 , and greater than one cm; had any inflammatory or chronic degenerative diseases, or demonstrated a body mass index (BMI) greater than 24.9 kg/m 2 on the day of the assessment. Finally, all subjects signed a formal consent form that was approved by the Ethics Committee on Research of the Universidade Federal de Juiz de Fora (n o : 321/2007), Juiz de Fora (MG), Brazil, and, when applicable, the consent form to the use of images.…”
Section: Samplementioning
confidence: 99%
“…Lower Limbs (LL) length measurements 21 With the subject positioned in supine position lying on a table, the examiner positioned himself besides the limb to be measured holding a 1.5 m tape measure with its extremity that initiated the marking between left hand's fi rst and second fi ngers, addressed cranially in relation to the subject. By palpation, the examiner ran his fi ngers anteriorly along the iliac crest to the ASIS and positioned the portion of the tape that initiated the marking over it.…”
Section: Instruments and Proceduresmentioning
confidence: 99%